2010
DOI: 10.1159/000280291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Bifidobacterium lactis</i> on the Incidence of Nosocomial Infections in Very-Low-Birth-Weight Infants: A Randomized Controlled Trial

Abstract: Background: Nosocomial infections endanger preterm infants. Objective: The aim of the present controlled randomized trial was to investigate whether Bifidobacterium lactis reduces the incidence of nosocomial infections in infants with very low birth weight (VLBW; <1,500 g) <30 weeks of gestation. Patients and Methods: In a randomized controlled trial, 183 VLBW infants <30 weeks of gestation were stratified according to gestational age (23–26 and 27–29 weeks) and early antibiotic therapy (days 1–3, yes or no) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 93 publications
(63 reference statements)
2
83
1
8
Order By: Relevance
“…Our finding of a lack of effect of the probiotic combination on definite lateonset sepsis is consistent with most, 14,[19][20][21][22][23][24][25][26][27][28][29] but not all, 13,28,[30][31][32] RCTs, as well as published systematic reviews and meta-analyses. [8][9][10] Interestingly, our study suggests a differential benefit of this probiotic combination on late-onset sepsis and possibly NEC of Bell stage 2 or more in infants born at 28 to 31 6 weeks' gestation.…”
Section: Discussionsupporting
confidence: 87%
“…Our finding of a lack of effect of the probiotic combination on definite lateonset sepsis is consistent with most, 14,[19][20][21][22][23][24][25][26][27][28][29] but not all, 13,28,[30][31][32] RCTs, as well as published systematic reviews and meta-analyses. [8][9][10] Interestingly, our study suggests a differential benefit of this probiotic combination on late-onset sepsis and possibly NEC of Bell stage 2 or more in infants born at 28 to 31 6 weeks' gestation.…”
Section: Discussionsupporting
confidence: 87%
“…We did not find any influence on culture-proven sepsis in our study using Infloran (Laboratorio Farmaceutico), which is in line with other investigations (19,32). As in other studies (33), sepsis with probiotic germs did not occur-neither in the study population nor in infants excluded from the study (data not shown)-which is reassuring.…”
Section: Probiotics For Necsupporting
confidence: 92%
“…The B. lactis used by Mihatsch et al 36 was checked monthly to ensure the viability and purity of the product together with the 24-hour stability of the prepared suspension. The six-strain product used by Fernández-Carrocera et al 40 (four strains of Lactobacillus, one of B. infantis and one of S. thermophilus) was checked twice against the manufacturer's quality control register and the ABC Dophilus used for the ProPrems trial 41 was imported under licence into Australia.…”
Section: Qualitymentioning
confidence: 99%